Policies and International Integration Influences on Trade and Foreign Direct Investment - Nicoletti, Giuseppe (OECD Publishing, 2003)
This paper assesses the importance of border and non-border policies for global economic integration. The focus is on four widely-advocated policies: removing explicit restrictions to trade and FDI; promoting domestic competition; improving the adaptability of labour markets; and ensuring adequate levels of infrastructure capital. The analysis covers FDI and trade in both goods and services, thus aiming to account for the most important channels of globalisation and dealing with most modes of cross-border services supply. It first describes trends in trade, FDI and the four sets of policies using a large set of structural policy indicators recently constructed by the OECD, including the new summary indicators for FDI-specific regulations described in Golub (2003). It then estimates the impact of policies on bilateral trade and bilateral and multilateral FDI. The results highlight that, despite extensive liberalisation over the past two decades, there is scope for further reducing ...
Keywords: Economics